Mapeamento de habitats como subsídios ao plano de manejo de unidades de conservação marinhas: o caso da APA Costa das Algas e refúgio da vida silvestre de Santa Cruz(Brasil) - Silva, Lídia Torquato da (2024)
From the initiative of civil society, through NGO, community associations, representatives of the fishing sector and residents, the APA Costa das Algas and the Wildlife Refuge of Santa Cruz was created by Federal Decree on June 18, 2010, in Espírito Santo. The rearing occurred mainly because it is a region with large physiographic varieties and predominant occurrence of carbonate sediments, including rhodolith bank and biodetritic sands. The aim of this study is to use the concept of habitats for the elaboration and characterization of thematic maps of the two environmental units: the Environmental Protection Area (APA) Algae Coast and the Wildlife Refuge (RVS) of Santa Cruz, so that they can be used for the elaboration of management plans. Methodologically, 50 points distributed in an area of 1580,330 km2 were defined, in which recognition was performed through filming by a remotely controlled vehicle (ROV), which was then analyzed to obtain the field truth. From the interpretation of all the information obtained, together with the survey of geophysical data and collection of sediment samples, carried out by the Project 'Detailed Study of the Ocean Bed inside the RvS of Santa Cruz, APA Costa das Algas and Immediate Surroundings of 2000m', we obtained twelve different types of habitats that make up the thematic map. Thus, the sum of the survey of all these attributes will produce a chart with all the habitats of the conservation units under study, enabling the association of habitats and coastal and marine ecosystems. With this, it will be possible to establish the differentiation of intensity of use through its zoning, aiming at the protection of natural and cultural resources. This survey can be used as a tool in the elaboration of the Management Plans of the two conservation units, so that the effective practice of the objectives established in its creation occurs, as well as its management with more effective measures in conservation and management, based on its sustainable development.